Educational change and innovative teaching practice : a study of the impact of reforms on the work of lecturers in vocational education and training in England and Germany - Ertl, Hubert [Verfasser]; Kremer, H.-Hugo [Verfasser] (My University, 2010)
"This paper focuses on the connection between system-wide reform in vocational education and training and the implementation of these reforms in learning and teaching processes. The study that is the subject of this paper conducted interviews with teachers in school-based vocational education in England and Germany. These interviews generated data on how teachers perceive reforms and in which ways they adapt their teaching as a result of reforms. This paper concentrates on the question in how far the interpretation of reforms by teachers leads to innovative processes at classroom level. The comparative design of the study aimed at identifying differences in innovative practice of teachers in Germany and England. It is concluded that the comparatively stable situation that German teachers find themselves in allow them to engage more actively in, and reflect more freely on, innovative practices than is possible for teachers in England. In contrast, innovative activities of teachers in England are often focused on the management of new teaching contents and the preparation for the teaching of a constantly changing portfolio of qualifications." (Autorenreferat, BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; L Lehren & Lernen; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufsbildung; Reform; Lehr-Lern-Prozess; Ausbildungsinhalt; Berufsschullehrer; Innovationsbereitschaft; Innovationsfähigkeit; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Bundesrepublik Deutschland; England